Evaluation of glass ionomer cements properties obtained from niobium silicate glasses prepared by chemical process - Bertolini, M. J.; Palma-Dibb, R. G.; Zaghete, M. A.; Gimenes, R. (Elsevier B.V., 2005)
Glass ionomer cements (GICs) are glass and polymer composite materials. These materials currently find use in the dental field. The purpose of this work is to obtain systems based on composition 4.5SiO(2)-3Al(2)O(3)-XNb2O5-2CaO to be used in Dentistry. The systems were prepared by chemical route at 700 degrees C. The results obtained by XRD and DTA showed that all systems prepared are glasses. The structures of the obtained glasses were compared to commercial material using Al-27 and Si-29 MAS NMR. The analysis of MAS NMR spectra indicated that the systems developed and commercial material are formed by SiO4 and AlO4 linked tetrahedra. The properties of glass ionomer cements based on the glasses prepared with several niobium contents were studied. Setting and working times of the cement pastes, microhardness and diametral tensile strength were evaluated for the experimental GICs and commercial luting cements. It was concluded that setting time of the cement pastes increased with increasing niobium content of the glasses (X). The properties to the GICs such as setting time and microhardness were influenced by niobium content. (c) 2005 Elsevier B.V. All rights reserved.